The Influence of Image Media And Puzzle Games on Conceptual Understanding (Research on Social Studies Lesson (IPS) at Elementary School) - Widyaningsih, Yennie Indriati; Muslihah, Neni Nadiroti; Pujiasti, Dea Asri; Nurseha, Alamsayah; Zahra, Febi Aulia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
Conceptual understanding is a person's ability to understand what is taught, capture the meaning of what is learned, and utilize the contents of the material being studied, as well as solve problems related to the material being studied. This study aims to determine the effect of using picture and puzzle media on conceptual understanding in social studies lessons in elementary schools. This research method is Quasi Experimental Design, this research instrument uses a test to measure conceptual understanding. The sample in this study was 20 students of class VA as the control class and 20 students of class VC as the experimental class. Data analysis techniques used the Normality Test, Homogeneity Test and t-Test. The results of the study showed that the application of picture media and puzzle games on students' conceptual understanding in social studies learning was better and showed a significant effect than those who did not use learning media. This is evidenced by the results of the hypothesis test, namely to 2.03> 1.90 for conceptual understanding. There is a difference between the control class and experimental class, the test results of the experimental class are greater than the control class. So it can be said that picture media and puzzle games can be used as an alternative in the learning process in the classroom.